Dietary Fiber Consumption and Colorectal Cancer: A Case-Control Study (Journal of Preventive and Social Medicine, 2023)
Background: Colorectal cancer (CRC) is an increasingly imperative cause of morbidity and mortality. This study aimed to determine the association between dietary fiber consumption and CRC.Methods: This age- and sex-matched case-control study was conducted from July 2020 to June 2021 at the Combined Military Hospital (CMH) and the National Institute of Cancer Research and Hospital (NICRH) in Dhaka. A total of 102 cases and 102 controls were selected through purposive sampling. Cases were adult patients diagnosed with CRC, while controls were individuals without cancer. Data were collected using a pretested semistructured questionnaire and checklist, which included information on socio-demographic characteristics, colorectal cancer attributes, and dietary fiber consumption. Face-to-face interviews were conducted to collect data from both cases and controls.Results: The mean (±SD) age of the cases and controls were 44.7±13.9 years and 45.6±13.3 years, respectively, with a male-female ratio of 1:1.3 in both groups. A significantly higher proportion of cases (53.9%) lived in joint families compared to controls (39.2%) (p=0.035). Type 2 diabetes mellitus (T2DM) was significantly more prevalent in cases (27.5%) than in controls (15.7%) (p=0.041) among the comorbid conditions. Majority of the cases (72.5%) consumed low dietary fiber (